Smeared Multiscale Finite Element Models for Mass Transport and Electrophysiology Coupled to Muscle Mechanics - Kojic, Milos; Milosevic, Miljan; Simic, Vladimir; Milicevic, Bogdan; Geroski, Vladimir; Nizzero, Sara; Ziemys, Arturas; Filipovic, Nenad; Ferrari, Mauro (Frontiers in Bioengineering and Biotechnology, 2019)
Mass transport represents the most fundamental process in living organisms. It includes delivery of nutrients, oxygen, drugs and other substances from the vascular system to tissue and transport of waist and other products from cells back to vascular and lymphatic network and organs. Further, movement is achieved by mechanical forces generated by muscles in coordination with the nervous system. The signals coming from the brain, which have the character of electrical waves, produce activation within muscle cells. Therefore, from a physics perspective, there exist a number of physical fields within the body, such as velocities of transport, pressures, concentrations of substances; and electrical potential which is directly coupled to biochemical process of transforming the chemical into mechanical energy and further internal forces for motion. The overall problems of mass transport and electrophysiology coupled to mechanics can be investigated experimentally and also theoretically by developing appropriate mathematical or computational models. Due to the enormous complexity of the biological system, it would be almost impossible to establish a detailed computational model for the physical fields related to mass transport, electrophysiology and coupled fields. In order to make computational models feasible for applications, we here summarize a concept of smeared physical fields, with coupling among them, and muscle mechanics which includes dependence on the electrical potential. Accuracy of the smeared computational models, and also with coupling to muscle mechanics, is illustrated with simple example, while their applicability is demonstrated on a liver model with tumors present. The last example shows that the introduced methodology is applicable to large biological systems.